2016
DOI: 10.1159/000443822
|View full text |Cite
|
Sign up to set email alerts
|

Histopathology of the Human Inner Ear in the p.L114P <b><i>COCH</i></b> Mutation (DFNA9)

Abstract: The histopathology of the inner ear in a patient with hearing loss caused by the p.L114P COCH mutation and its correlation with the clinical phenotype are presented. To date, 23 COCH mutations causative of DFNA9 autosomal dominant sensorineural hearing loss and vestibular disorder have been reported, and the histopathology of the human inner ear has been described in 4 of these. The p.L114P COCH mutation was first described in a Korean family. We have identified the same mutation in a family of non-Asian ances… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
27
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 21 publications
(27 citation statements)
references
References 20 publications
0
27
0
Order By: Relevance
“…Aggrecan (extracellular component of cartilage), S100 and connective tissue growth factor were detected in the human temporal bones from individuals diagnosed with DFNA9 (McCall et al 2011). Changes in neurofilaments and myelin protein zero antibodies were detected in the cochlea of a patient with hearing loss caused by the p.L114P COCH mutation (Burgess et al 2016). Recent studies that apply IHC in human inner ear celloidin-embedded sections have shown the presence of specific markers for macrophages/microglia: CD163 + , Iba1 + and CD68 + (O’Malley et al 2015).…”
Section: Discussionmentioning
confidence: 99%
“…Aggrecan (extracellular component of cartilage), S100 and connective tissue growth factor were detected in the human temporal bones from individuals diagnosed with DFNA9 (McCall et al 2011). Changes in neurofilaments and myelin protein zero antibodies were detected in the cochlea of a patient with hearing loss caused by the p.L114P COCH mutation (Burgess et al 2016). Recent studies that apply IHC in human inner ear celloidin-embedded sections have shown the presence of specific markers for macrophages/microglia: CD163 + , Iba1 + and CD68 + (O’Malley et al 2015).…”
Section: Discussionmentioning
confidence: 99%
“…All patients were selected from cases without other bone disease such as osteoporosis or Paget's disease and without inflammatory disease such as otitis media and labyrinthitis and they classified into 4 groups: histologically proven SSCD (n = 3, group 1), age 20 years or younger (n = 10, group 2), age 90 years or older with otosclerosis (n = 10, group 3), and age 90 years or older without otosclerosis (n = 10, group 4). The clinical histories of cases 1 and 2 with SSCD (group 1) have already been reported [Teixido et al, 2012;Burgess et al, 2016]. The clinical history and histologic findings of case 3 (group 1) are presented herein.…”
Section: Subjectsmentioning
confidence: 91%
“…The organ of Corti (OC) was seen. Source: Previously published 33 and reprinted with permission of Karger Publishers F I G U R E 7 Immunostaining following celloidin removal with methanol, saturated with sodium hydroxide. Immunostaining for six antibodies was accomplished.…”
Section: Molecular Genetics and Histochemical Localization In Otopamentioning
confidence: 99%
“…Sanger sequencing of DNA can also be accomplished using frozen muscle obtained at autopsy of a temporal bone donor. Using this technique, the histopathology of the human inner ear caused by the p.L11p Coch mutation (DFNA9) was demonstrated (Figure ).…”
Section: Introduction Of New Techniques In Otopathologymentioning
confidence: 99%
See 1 more Smart Citation